67‐1: Invited Paper: Design of an Advanced Bottom‐emission AMOLED Display for TVs with High‐PPI and Large Size. Issue 1 (29th May 2019) - Wu, Yuan-Chun; Xue, Yan; Han, Bai-Xiang; Chaw, Gary; Lin, Zhen-Guo; Hsu, Yuan-Jun; Fu, Jian-Hang; Hwang, Tai-Jiun; Lu, Po-Yen
Abstract : Top‐gate typed amorphous‐indium‐gallium‐zinc‐oxide (a‐IGZO) thin‐film‐transistors (TFTs) and a technologically advanced transparent storage capacitance structure have been successfully employed in pixel circuits. The design procedure was systematically studied. Eventually, a 15‐inch gate‐driver‐on‐array (GOA) drived active matrix organic light‐emitting diode (AMOLED) display was demonstrated with a high resolution of 147 ppi.